The ends of polemic and the beginning of 'Lohengrin' - Matthews, A (Ashgate, 2015)
The depiction of poetic rivalry in works of art has a long tradition behind it. This chapter from an anthology of essays on polemic in medieval and early modern Europe examines its role in the opening strophes of the Middle High German 'Lohengrin'. They depict a confrontation between Wolfram von Eschenbach and Clinschor that supposedly took place at the court of Landgrave Hermann I of Thuringia in the early thirteenth century. The chapter traces the strategies of polemic speech and forms of resolution in these strophes, and shows how they lead to sources of coherence that have been overlooked in the derivative interpretations of previous studies.